A SIR-based communication paradigm for realization of molecular nanonetwork - Chen, Ya Fen. (2012)
Advancements in nanotechnology have enabled the fabrication of simple nano-machines with very limited sensing, computation, communication, and action capabilities. In order to develop more effective application, nanonetworks which are the networks of communicating nano-machines need to be designed. Therefore, it can be used to accomplish complex tasks such as drug delivery and health monitoring.